Predictors of quit attempts among smokers enrolled in substance abuse treatment. (January 2015) - Martínez, Cristina; Guydish, Joseph; Le, Thao; Tajima, Barbara; Passalacqua, Emma
Abstract: Introduction: This study investigates factors predicting past year quit attempts among smokers enrolled in substance abuse treatment in New York State. Methods: Data were drawn from two prior cross-sectional surveys conducted among clients treated in 10 randomly selected substance abuse treatment programs. Among 820 clients recruited, 542 self-identified as current smokers, and 485 provided information about their quit attempts. The main outcome was reporting a quit smoking attempt in the past year, dichotomized as quit attempters or non-quit attempters. Univariate and multivariate logistic regression analyses were performed to explore predictors of attempting to quit. Results: Half of substance abuse clients in treatment programs reported a past year quit attempt. Quit attempters were more likely to be in a preparation and contemplation stage of change (preparation: OR = 2.68, 95% CI: 1.51–4.77; contemplation: OR = 2.96 95% CI: 1.61–5.42), reported more positive attitudes toward quitting (OR = 1.49; 95% CI: 1.11–1.99) and received more cessation services than non-quit attempters (OR = 1.21; 95% CI: 1.11–1.99). Conclusions: Addressing patient attitudes about quitting smoking, having clinicians address smoking in the course of addiction treatment, and offering interventions to increase readiness to quit may contribute to increased quit attempts in smokers enrolled in addiction treatment programs. Highlights: This study explores for the first time quit attempts among smokers in addition treatment in New York the first U.S state that required all certified addiction treatment programs to implement tobacco-free grounds and tobacco dependence interventions. Data shows that half of smokers in addition treatments reported at least one past-year quit attempt. This finding confirms that persons in addiction treatment are as interested in quitting as smokers from the general population. This study adds to the scarce literature on quit attempts, that both clinician services and favorable patient attitudes toward quitting can increase quit attempts in this population.